PSYCHOANALYTIC INTERPRETATION AS A RESEARCH METHOD FOR STUDYING MILITARY DISCOURSE - Tatyana E. Khraban (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The aim of the article is to substantiate the methodological guideline of using psychoanalytic interpretation in the research strategy of modern Ukrainian non-institutional military discourse on the Internet communication. Materials & methods. General scientific research methods: analysis, classification, systematization, explanation were used to achieve the goal. Results and discussions. The use of psychoanalytic interpretation as a scientific method of psychoanalysis becomes crucial for the study of Ukrainian non-institutional military discourse. Psychoanalytic interpretation focuses on accentuation of senses and the assumption of self-sufficiency experience. Psychoanalytic interpretation includes two stages: understanding and explanation. Understanding involves the researcher’s ability to understand the individual (group) socio-psychological characteristics and requires knowledge of the service condition features, which are military-related for these group members. On the second stage (the explanation of understanding) planned or committed actions are considered in the perspective of causality, i. e. they are analyzed through the prism of motivation. An explanation is considered to be correct if the reasons (incentives) emphasized in the explanation not only existed, but were also productive. Moreover, the explanation is not just a formal (mechanical) process of finding motivation, but also includes assessment. Possible presentation of Ukrainian non-institutional military discourse in the Internet communication in the form of stories, descriptions, reflections, digressions characterized by expressive composition as well as in the form of military poetry of the participants of Joint Forces operation, requires recourse to psychoanalytic literary studies. In this case, psychoanalysis focuses on the symbolism of the unconscious, universal meanings and the psychological mechanisms manifestation that are important material for the study. Conclusions. Formed by a combination of different types of discourses modern Ukrainian noninstitutional military discourse needs a special methodological tool for its analysis. The research task success significantly depends on the correct choice of methods. The emphasis on the psychological features of the speaker, i.e. the inclusion of a wide range of factors: psychological, mental, pragmatic etc. in the linguistic personality analysis requires the use in the research strategy of psychoanalytic interpretation as a scientific method of psychoanalysis.